Hardness and fracture toughness analysis of ZTA–SWCNT ceramic cutting inserts - Hamidon, Nor Ezzati; Abdul Molok, Salma; Manshor, Hanisah; Ahmad Azhar, Ahmad Zahirani; Rejab, Nik Akmar; Ahmad, Zainal Arifin; Mohd Ali, Afifah (American Institute of Physics Inc., 2019)
Hardness and fracture toughness of ZTA samples with addition of SWCNT have been investigated. The composition of Al2O3/YSZ was constant at 80:20 ratios with the amount of SWCNT varied from 0.00, 0.05, 0.10, 0.30 and 0.50 wt %. The SWCNT was soaked in 20 ml ethanol and dispersed using ultrasonic agitation for 1 hour prior to addition with Al2O3/YSZ powder using wet mixing. The hardness and fracture toughness were calculated using Vickers indentation techniques. The Vickers hardness results show that presence SWCNT causes agglomeration in the microstructure of ZTA matrix as a result decreased hardness value. Meanwhile the fracture toughness of ZTA with 0.50 wt. % SWCNT increased to 6.593 MPa·√m which is the highest value. In addition, the good dispersion of CNTs in ZTA matrix composites is with addition 0.10 wt. % of SWCNTs.